Date palm fruit (Phoenix dactylifera L.): structure, ripening, nutrition, and applications - Manan Ashok Sejpal; Linghong Shi; Rongjia Xie; Kashif Ghafoor; Farhad Ahmadi; Hafiz A.R. Suleria (Discover Chemistry)
Abstract Date palm is an important plant mainly cultivated in arid regions such as the Arabian Peninsula, North Africa, and the Middle East. The vital product of the date palm is its fruit, which is highly valued and consumed in various forms, including fresh, dried, or processed. Date palm fruits, along with their seeds, are rich in essential nutrients, such as vitamins, minerals, dietary fiber, and antioxidants, which contribute to their significant health-promoting properties. This comprehensive review provides a detailed description of structural composition, and maturation process of the date palm fruit. It presents an in-depth nutritional profiling of each anatomical part of the fruit, with emphasis on key constituents such as polyphenols, carbohydrates, dietary fiber, and essential minerals. Furthermore, this review discusses the potential applications of various parts of the date palm in different industries, including food, pharmaceuticals, and cosmetics. Challenges impeding the broader utilization of these resources are discussed, and potential strategies for overcoming these barriers are proposed.